Impact of surface roughness on the adhesion strength of PVA/eggshell-derived hydroxyapatite coatings on AISI 316L substrates - Mochamad Arif Irfa'i; Suherman Suherman; Achmad Fadjar Maulana Firdaus (Jurnal Polimesin, 2026)
This study investigates the effect of AISI 316L surface roughness on the adhesion Poly Vinyl Alcohol (PVA) and eggshell-derived Hydroxyapatite (HA) coatings applied via slurry spraying. The surfaces were modified by the sandblasting method resulting in a maximum roughness of 4.803 µm using 16-30 mesh SiO2 as sandblasting media. Reducing SiO2 particle size to 30-60 mesh and subsequently 60-80 mesh, gradually reduces the surface roughness to 3.431 µm and 1.712 µm, proving that smaller abrasive particles result in a smoother surface. The slurry spraying process was then done using 27:73 mass-based mixture of HA and 3% PVA solution in water. Results revealed that while sandblasting significantly altered substrate topography, the resulting coatings remained dense and pore-free with consistent thickness across all roughness levels, while maximum adhesive strength of 4.09 MPa based on ASTM D4541 method was observed in the specimen sandblasted with 30-60 mesh SiO2, corresponding to a Ra value of 3.43 µm. Utilizing sustainable eggshell-derived HA provides a bioactive, cost-effective coating material that achieves high inter facial adhesion on AISI 316L, offering a mechanically stable and affordable solution for the development of next-generation orthopedic implants.